2013
DOI: 10.3109/09537104.2013.857394
|View full text |Cite
|
Sign up to set email alerts
|

Mean platelet volume and mean platelet volume/platelet count ratio in infective endocarditis

Abstract: Infective endocarditis (IE), an infection of the endocardial surface, frequently leads to life-threatening complications, such as thromboembolism due to platelet activation. We investigated the mean platelet volume (MPV) in Korean patients with IE and the serial changes thereof, in comparison with other laboratory parameters. We analyzed 248 MPV results from 22 patients diagnosed with IE in our hospital between January 2011 and April 2012. MPV was measured with an Advia 2120 (Siemens Healthcare Diagnostics, Ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 15 publications
0
35
2
Order By: Relevance
“…Mean platelet volume/PC ratio has been shown to be higher in thromboembolic diseases such as deep vein thrombosis and infective endocarditis. [14,15] Azab et al [13] has shown that long-term infarctioncaused mortality rate is significantly higher in patient groups with very high (40 and more) and very low (30 and less) MPV/PC ratios compared to moderately higher patient group (MPV/PC ratios of 30-40). The authors mentioned that very high MPV/PC rates resulted from extremely high MPV levels (along with elevated platelet aggregation and activation) as well as from significant decreases in platelet number.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mean platelet volume/PC ratio has been shown to be higher in thromboembolic diseases such as deep vein thrombosis and infective endocarditis. [14,15] Azab et al [13] has shown that long-term infarctioncaused mortality rate is significantly higher in patient groups with very high (40 and more) and very low (30 and less) MPV/PC ratios compared to moderately higher patient group (MPV/PC ratios of 30-40). The authors mentioned that very high MPV/PC rates resulted from extremely high MPV levels (along with elevated platelet aggregation and activation) as well as from significant decreases in platelet number.…”
Section: Discussionmentioning
confidence: 99%
“…Higher MPV/PC ratio is associated with myocardial infarction, anemia, deep vein thrombosis, infective endocarditis and hepatocellular carcinoma. [13][14][15][16] There are limited studies pointing to the association between adenoid hypertrophy and MPV in pediatric OSAS. [10,17] However, to our knowledge, there is no study in the literature dealing with the association between pediatric OSAS and MPV/PC.…”
mentioning
confidence: 99%
“…In patients with infective endocarditis, higher MPV values than controls, MPV levels over 8.6 fl on admission as a strong independent indicator of embolic events and in-hospital mortality, increasing trends for MPV levels associated with adverse events and mortality, reduction in MPV levels by treatment have been demonstrated [5,19].…”
Section: Mpv and Infective Endocarditismentioning
confidence: 99%
“…Meanwhile, other previous study reported that PDW and MPV were not correlated with AS activity [21,22]. We assumed that the diverse confounding factors to affect PDW and MPV levels might result in these discrepancies [11][12][13][14][15][16][17][24][25][26]. With these reasons, in the present study, we excluded patients with AS who had abnormal laboratory results, and who had medical conditions such as hematologic diseases or history of medication administered affecting PDW and MPV such as antiplatelets [25,28] (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…We consecutively screened and enrolled 141 patients with AS in this study, from March 2015 to October 2015, by the inclusion criteria as follows: (1) patients who fulfilled modified New York criteria for AS and who had been first diagnosed with AS at the Division of Rheumatology, Yonsei University College of Medicine, Severance Hospital [23]; (2) patients who had no medical conditions to affect PDW and MPV, such as abnormal glucose metabolism, chronic liver diseases, chronic kidney diseases, hypertension, dyslipidaemia, cardiovascular diseases, rheumatoid arthritis, and concurrent infection or hematologic disorders identified by 10th revised international classification of diseases [11][12][13][14][15][16][17]24,25]; (3) patients who had never received medications for diseases above searched by the Korean Drug Utilization Review system; (4) patients who had not received blocking agents against tumour necrosis factor (TNF), which are one of factors influencing the maturation of thrombopoietic cells and release of platelet into the circulation [26]. (5) Patients who had no concurrent infection and malignancy to enhance acute phase reactants levels; (6) patients who gave informed consent to their participation; (7) patients who took the assessment of disease activity indices of AS by independent physician on the same day of laboratory tests; (8) patients having laboratory results fulfilling the normal reference range as described in Figure 1 [27].…”
Section: Patientsmentioning
confidence: 99%